HIV/AIDS and modernity in Africa: a philosophical perspective - Cloete, Michael (Acta Academica: Critical views on society, culture and politics, 2008)
HIV/AIDS poses the greatest threat to human life in sub-Saharan Africa. Although the general awareness of the various modes of HIV-transmission has increased significantly over the past few years, the continuing threat of this deadly disease seems to be unstoppable. To make matters worse, our understanding of HIV/AIDS has been dominated by Western philosophical discourses that somehow question Africa’s ability to understand fully the serious nature and extent of the HIV/AIDS pandemic. This article addresses the possibility of Africa’s right to life from the perspective of the philosophical discourse of modernity in Africa.